Solar UV-B radiation modulates chemical defenses against Anticarsia gemmatalis larvae in leaves of field-grown soybean - Dillon, Francisco María (2017)
Although it is well known that solar ultraviolet B (UV-B) radiation enhances plant defenses, there is less knowledge about traits that define insect resistance in field-grown soybean. Here we study the effects of solar UV-B radiation on: a) the induction of phenolic compounds and trypsin proteinase inhibitors (TPI) in soybean undamaged leaves or damaged by Anticarsia gemmatalis neonates during six days, and b) the survival and mass gain of A. gemmatalis larvae that fed on soybean foliage. Two soybean cultivars (cv.), Charata and Williams, were grown under plastic with different transmittance to solar UV-B radiation, which generated two treatments: ambient UV-B (UVBþ) and reduced UV-B (UVB) radiation. Solar UV-B radiation decreased survivorship by 30% and mass gain by 45% of larvae that fed on cv. Charata, but no effect was found in those larvae that fed on cv. Williams. TPI activity and malonyl genistin were induced by A. gemmatalis damage in both cultivars, but solar UV-B radiation and damage only synergistically increased the induction of these compounds in cv. Williams. Although TPI activity and genistein derivatives were induced by herbivory, these results did not explain the differences found in survivorship and mass gain of larvae that fed on cv. Charata. However, we found a positive association between lower larval performance and the presence of two quercetin triglycosides and a kaempferol triglycoside in foliage of cv. Charata, which were identified by HPLC-DAD/MS2 . We conclude that exclusion of solar UV-B radiation reduce resistance to A. gemmatalis, due to a reduction in flavonol concentration in a cultivar that has low levels of genistein derivatives like cv. Charata.